Disaggregated pluralistic theories of global distributive justice – a critique. Issue 2 (4th May 2017) - Culp, Julian
ABSTRACT: Pluralistic theories of global distributive justice aim at justifying a plurality of principles for various subglobal contexts of distributive justice. Helena de Bres has recently proposed the class of disaggregated pluralistic theories, according to which we should refrain from defending principles that apply to the shared background conditions of such subglobal contexts. This article argues that if one does not justify how these background conditions should be regulated by principles of a just global basic structure, then the (apparent) realization of the principles that are justified for the subglobal contexts of distributive justice can erode and undermine justice over time. For example, the realization of justice in international trade might undermine climate justice, at least if climate justice requires increasing tariffs (in order to mitigate greenhouse gas emissions) but justice in international trade calls for reducing tariffs (in order to create a level playing field). Principles of a just global basic structure would have to ensure that such justice-eroding spillover effects from one to another context of justice do not occur. Finally, the article responds critically to de Bres' objections that an account of a just global basic structure is too idealistic, not action guiding, and superfluous.